Relationship Betveen s Maximal Radar Reflectivity of Frontal Convective Clouds ofKakheti Rregion of Georgia From Mean Intensity of Atmospheric Precipitation - Salukvadze, Tamaz G.; Khelaia, Eteri I.; Salukvadze, Marine T. (Journals of Georgian Geophysical Society, 2017)
The dates of radar observations by convective clouds of a warm season are parsed. They were carried out in Kakheti region of Georgia at passing cold atmospheric fronts. The values of radar reflectivity (Z) of these clouds was compared to intensity of the dropped out atmospheric precipitation The empirical relationship between these meanings was retrieved. The reliability coefficient of the retrieved relationship is equaled 0,59 at confidence probability 0,93.